Studying the Mechanism of Creatinine Biosynthesis and the Effect of Its Disorders on the Animal Body - Rahimi, Manizha (Journal of Natural Sciences – Kabul University, 2023)
The most important derivatives of amino acids are urea, creatine, creatinine and amines. Creatinine is a product obtained from the breakdown of creatine phosphate and muscle and protein metabolism. Creatine loses a molecule of water in an acidic environment field and turns into creatinine. These substances are available in muscle, brain and blood both in the form of creatine phosphate and in free form. In the biosynthesis of creatine, three amino acids - glycine, arginine and methionine - are directly involved, synthesis of creatine in the liver by methylation of glucosamine. Any condition that disrupts the function of the kidney increases the level of creatinine in the blood. A low level of creatinine can indicate poor metabolic health of muscles or severe liver disease; high levels of creatinine are related to protein.